A Treament Approach To Class 3 Open-Bıte Event - Ali S. Gültan (Galenos Yayinevi, 1990)
Class 3 open bite cases are multi dimensional complex anomalies. The prognosis of the treatment of these anomalies are not entirely successful. Accordingly, several treament approaches are being argued. For a successful treatment, different views are reported in accordance with the ethiology, degree of anomaly, growth and development conditions. In this article, several approaches concerning class 3 open bite treaments are discussed; a case treated by means of extraction of first molars and application of fixed appliances is provided.